Kappa-Distributed Electrons in Solar Outflows: Beam-Plasma Instabilities and Radio Emissions - Lopez-Escobar, R (Springer Science and Business Media B.V., 2023)
Electrostatic (ES) wave instabilities are assumed to be at the origin of radio emissions from interplanetary shocks, and solar coronal sources are most likely induced by electron beams, more energetic but less dense than electron strahls in the solar wind. In this paper, we present the results of a new dispersion and stability analysis for electron populations with Kappa velocity distributions, as often indicated by in situ observations. We investigate, both theoretically and numerically, three electron plasma beam configurations with different implications in the generation of radio emissions. The same three cases, but for Maxwellian distributed electrons, were considered in numerical simulations by Thurgood and Tsiklauri (Astronomy and Astrophysics 584:A83, 2015). Our kinetic plasma approach clarifies the nature of the unstable mode as being an electron beam ES instability (and not a Langmuir instability) in all cases, and for both Kappa and Maxwellian approaches. Electron beam waves are Landau resonant and with frequencies of the fastest growing modes close to but below the plasma frequency (i.e., ω≲ ωpe ). Suprathermal Kappa tails tend to inhibit the instability by reducing the growth rates, but these effects become minor if the drift speed of the beam is sufficiently high compared to the thermal speed of the electrons. The frequency downshift, also revealed by the observations, clearly tends to increase in the presence of a Kappa-distributed beam. Particle-in-cell (PIC) simulations confirm the inhibiting effects of (initially) Kappa-distributed electrons, but these minor effects in the linear and quasi-linear phases unexpectedly lead to significant decreases in the wave energy levels of the (primary) ES fluctuations near the plasma frequency and higher harmonics. As a result, EM radio (secondary) emissions generated nonlinearly after saturation are even more drastically reduced and can even be completely suppressed. However, the EM emissions around the second harmonic (ω≲2ωpe ) are markedly powered by two symmetric countermoving beams, even in the presence of Kappa electrons. These results offer real promise for a realistic interpretation and modeling of radio emissions observed in heliosphere, arguing in favor of a rigorous spectral analysis of the wave instabilities at their origin. © 2023, The Author(s), under exclusive licence to Springer Nature B.V.